The Promotion of Ex Officio in the Execution Stage in Minor Labor Processes - Vásquez Rosales, Karol (2024)
This work has been prepared with two objectives. The first is to expose the reasons why ex officio promotion in the execution stage of labor processes is an obligation of judges to make the right to effective jurisdictional protection a reality. The second is to present the practice of this ex officio impulse in a labor lawyer's peace court and the consequences of it. From these purposes, the conclusion was reached that, due to the right to jurisdictional protection contained in various legal, constitutional and conventional mandates, the judge has the intrinsic obligation to necessarily ensure the effectiveness of the sentences, a task that must be carried out trade, in such a way that in addition to generating the material satisfaction of the winner of the process, it helps to improve confidence in the Judiciary. Additionally, for said informal execution, judges have various legal powers; informal work that will only be carried out by those judges convinced that effective jurisdictional protection is a fundamental right. Finally, based on the practice of the ex officio initiative in a peace court with a labor lawyer shown in this work, it was evident that the judicial processes have been successfully completed with full execution of the sentence in a period of less than one year.